Novel models of dementia care: Evidence from national dementia behavior support programs in Australia. (31st December 2021) - Atee, Mustafa; Morris, Thomas; Macfarlane, Stephen; Alford, Marie; Cunningham, Colm
Abstract: Background: Behaviors and psychological symptoms of dementia (BPSD) are frequently experienced by this population, as they reflect unmet biopsychosocial needs.[1] The occurrence of BPSD can be debilitating, distressing and impair quality of life, not only for the person living with dementia but also for their caregivers.[1] As such, people with BPSD have complex care needs that demand dedicated resources, tailored programs and specialized skills which are often missing in mainstream aged care services. To address these needs and to achieve a nationally consistent approach, the Australian Government has been funding the services of Dementia Support Australia (DSA). DSA is the leading national provider of 24/7 dementia‐specific behavior support programs in Australia. DSA programs include the Dementia Behavior Management Advisory Service (DBMAS) for mild‐moderate BPSD and the Severe Behavior Response Teams (SBRT) for moderate‐severe BPSD. These programs entail person‐centered and multimodal nonpharmacological, psychosocial and/or psychoeducational interventions to support people with BPSD and their caregivers. These are achieved through a case management framework that includes an onsite comprehensive/holistic assessment of medicosocial history (e.g. pain), surrounding environment (e.g. over/under‐stimulation) and prescribed medications to identify causes or triggers of BPSD (Figure 1).[1] DSA is delivered through a multidisciplinary and mobile workforce of dementia consultants, geriatricians/psychogeriatricians and support staff. DSA consultants are accredited against an industry‐specific program focused on dementia‐specific competencies and capabilities. Consultants include, but are not limited to, registered and mental health nurses, occupational therapists, physiotherapists, social workers, psychologists, dieticians, speech pathologists, and diversional therapists with significant experience working in dementia and aged care settings. Since establishment in 2016, DSA programs have supported over 30, 000 client referrals from residential, community and acute care settings and have supported >80% of residential aged care homes in Australia. Typical demographics for DBMAS and SBRT clients are displayed in Figure 2. Data collected on referrals demonstrated reduced frequency and severity rates of BPSD and high levels of caregiver satisfaction. Thus, DSA programs provide a novel, effective, feasible and sustainable model of care and service delivery specifically designed to address perceived gaps in aged care systems. References [1] The IPA complete guides to BPSD‐Specialists guide. Northfield (Illinois) 2012.